Controle da formação de escuma e remoção de matéria orgânica em reator UASB com duplo estágio de coleta de biogás - Jackson de Oliveira Pereira (2007)
The present study tested the potential of application of a UASB reactor equipped with a double stage of biogas collection, treating domestic sewage, for the control of scum formation and removal of organic matter. For this, two UASB reactors in pilot scale had been compared in terms of the scum formation control and the performance of organic matter removal. One of the reactors was modified and confectioned with a similar conception of a IC reactor (Internal Circulation), with a first stage of biogas collection located next to the bottom. The other one, used as control, was a conventional UASB reactor. The modified reactor allowed the exit of all scum from the reactor, and the conventional UASB reactor held back all the scum formed in the three-phase separator and in the settlers. The reactors were inoculated with flocculent sludge and were operated in three distinct phases. During the start-up the reactors, modified and controlled one, were operated with a HRT of 7 and 10 hours, respectively, after that both reactors were operated with a HRT of 7 hours throughout the remaining operational period. The results had showed that the modified UASB reactor was capable to keep the typical performance of a conventional UASB reactor, not presenting limitations to its application under this aspect, with average removal efficiencies of 65% for BOD, 60% for COD and about 85 to 90% for filtered COD. The modified reactor was more effective than the convencional one in the control of scum formation, due to the possibility of occurrence of scum degradation and or its disaggregation and exit from the inner part of the three-phase separator, in this reactor configuration. Additionally, other potential advantages had been revealed by this configuration, as sludge granulation, higher methane production rate, and robustness to the rise of the particulate fraction in the affluent. Thus, this configuration, in function of the presented potential advantages, can represent an advance in the technological development of UASB reactors treating domestic sewers.